Gender Differences in Ethical Investment Behaviour Among Islamic Capital Market Investors - Cintiya Anggita, Marsa; Daryono; Karim, Abdul (Inovasi Analisis Data, 2025)
Objective: This paper investigates the influence of gender, financial literacy, risk perception, and religious commitment on ethical investment behavior moderated by financial experience. Methods: The model was tested through a quantitative explanatory approach grounded on behavioral finance and Sharia law-based paradigms. Results: It is found that gender, financial literacy, risk perception and religious commitment have an influence on ethical investment behavior can be significantly affected by to financial experience. Ethical investors are more strongly committed to Sharia principles and a socially responsible portfolio when they make decisions based on moral awareness - Moral aware investment, as well as from experiential learning – Experiential moral learning. The model confirms the behavioral finance theory in an Islamic ethical environment and sheds light on how the cognitive–spiritual dimension affects investment decisions. Novelty: This study combines the behavior of finance literature with the Islamic ethical paradigm and supports that financial experience accentuates the moral side of investment decisions through enhanced judgment and ethical sensitivity. Research Implication: The findings provide policymakers and Islamic financial institutions with an empirical basis to initiate experience-based education and gender inclusiveness programs to enhance ethical financial eco-systems, and enhance the sustainability of Sharia investment behavior world over.